Physico-chemical and microbiological characteristics of the Apis mellifera L. honey of from different warehouses - Santos, Dyego da Costa; Oliveira, Emanuel Neto Alves de (Comunicata Scientiae, 2013)
The state of Ceara excels in the national scene as one of the largest producers of honey, what makes it important the monitoring of the quality of bee products processed in the warehouses. The objective of this study was to characterize honeys of Apis mellifera L. from seven apiaries located in the region of Vale do Jaguaribe, Ceará. The honeys were analyzed as for apparent sucrose, reducing sugars, acidity, pH, moisture, insoluble solids, ash, coliforms at 35° and 45 °C, yeasts,molds and Salmonella spp. According to the results of physic-chemical, all honeys evaluated where in accordance with Brazilian legislation, with significant effect at 1% probability for all physic-chemical parameters evaluated, demonstrating the heterogeneity of these characteristics. The samples analyzed were not contaminated by coliforms at 35° and 45 °C and Salmonella spp., showing a low number of yeasts and molds. According to the results of the parameters specified by legislation, the beekeepers performed the management, the harvesting and the processing of these bee products as recommended in order to obtain a qualified product.